PENDAMPINGAN UMKM GO EXPORT BERBASIS E-COMMERCE - Putri, Alfina Syahara; Anggraeni, Rahayu Indah; Hani’ah, Umi; Kusuma, Andre Wahyu; Wijayanti, Dini Astri; Komariyah, Erna Fitri; Wijayanti, Lilis Endang (COMMENT: Journal of Community Empowerment, 2024)
Technological developments in business offer promising opportunities. However, not all business actors, such as SMEs, can follow these developments easily. E-commerce as an electronic medium in trade activities provides space and various facilities that are mutually beneficial. The low number of e-commerce business actors in Indonesia, especially in Yogyakarta, aligns with the number of information technology utilization training that has been obtained. This community development aims to help SME business actors expand their market share by opening and managing online e-commerce stores using the Shopee platform. This service uses a case study method with Toko Oblong Walang as an object. Starting with registering a seller account, how to get orders through efforts to increase product and store visibility has also been done and conveyed to business owners. Finally, after four months of service, registration to Shopee Export was successful. The results of this service show that not all technological developments can be easily followed by SME business actors. Training, mentoring, and coaching can be carried out as community development. In addition, increasing product and store visibility is important so potential buyers can convert into buyers.